THE ROLE OF ISLAMIC BANKING SERVICE QUALITY ON CUSTOMER SATISFACTION IN INCREASING CUSTOMER RETENTION - Sulistiyawan, Edy; Suharyanto, Suharyanto; Zuhroh, Rena Sofyatus; Putri, Zahra Regita Amelia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The increasing level of public awareness of the alternative banking system with the iB logo (read ai-Bi, Islamic banking) is part of the results of intensive socialization by regulators over the past few years. Like a ripe fruit, this public enthusiasm is ready to be picked by Islamic banks that are observant and quick to capture market opportunities. And if that happens, it is not impossible that iB (Islamic Banking) will accelerate even faster than its growth so far which has been very impressive reaching 46.3% per year. researchers try to confirm the relationship between CARTER+ service quality, satisfaction, and retention in the context of Islamic banks in Indonesia. In addition, it is necessary to study more deeply about customer retention in enjoying Islamic banking products and services. In accordance with the function of the bank, namely establishing relationships with customers, it is able to create value that is felt directly by customers. This can foster long-term satisfaction and encourage customers to remain customers of the bank. one of the most important factors for customers to continue using bank products and services, the company must maintain the level of customer retention. In this study, the measurement model used is expected to, firstly, assist decision making in Islamic banking marketing and to identify determinants of the quality of Islamic banking services, better known as Islamic Banking Service Quality (iBSQ). Secondly, customer satisfaction of Islamic state-owned banks is a direct response given by bank customers to the dimensions of Islamic state-owned bank service quality, which in the end can significantly increase customer retention. Thirdly, customer retention is the ultimate goal of all services from Islamic banking in general and Islamic state-owned banks in particular. In this study, the approach used is a quantitative approach (positivism) supported by informative qualitative. The data used are primary and secondary data. The SEM-PLS method applied to data processing is expected to be able to provide the expected information. In this study, the data sources were taken from 3 different banks, namely: Bank BRI Syariah, Bank BNI Syariah and Bank Syariah Mandiri. Based on the results of the analysis and discussion of this study, the following conclusions can be drawn: (1) Of the seven dimensions of service quality that have a significant influence on customer satisfaction, the Sharia Compliance dimension is 19.3%, the Service System dimension is 28.4%, the Responsiveness dimension is 30.6% and the remaining 21.7% is influenced by other variables that are not included in the model. (2) Customer retention is significantly influenced by Customer Satisfaction by 28.2% while the remaining 71.8% is influenced by other variables.